Ryzyko katastroficzne - zarys problematyki - Wierzchowska, Kinga (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
More and more common problem faced by insurance companies is disaster damage. Increasing costs resulting from disasters are becoming a big threat to insurers. Ordinary protection methods are no longer satisfactory. Combining the insurance and finance markets enables gaining extra capital thus protecting oneself from the insurer's insolvency. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 481-486